Economic evaluation of a hypothetical screening assay for alloimmunization risk among transfused patients with sickle cell disease. Issue 8 (27th February 2014) - Kacker, Seema; Ness, Paul M.; Savage, William J.; Frick, Kevin D.; Shirey, R. Sue; King, Karen E.; Tobian, Aaron A.R.
<x xml:space="preserve">Abstract</x> Background Prophylactic antigen‐matching can reduce alloimmunization rates among chronically transfused patients with sickle cell disease (SCD), but this matching increases costs and may only benefit 30% of patients. We assessed the clinical and financial value of a potential assay for alloimmunization risk that would allow for targeted antigen‐matching. Study Design and Methods A Markov‐based model evaluated direct medical costs and alloimmunization events over 10 to 20 years among transfused (simple or exchange) patients with SCD. Four matching strategies were evaluated: prospective matching (for all patients), history‐based matching (only for patients with prior alloimmunization), perfectly informed matching (assay with 100% sensitivity, 100% specificity), and imperfectly informed matching (reduced accuracy). Under all matching protocols, matching included C, E, K, and any additional alloantibodies present. A hospital perspective was adopted, with costs (2012US$) and events discounted (3%). Results Perfectly informed antigen‐matching using a $1000 assay is expected to save $82, 334 per patient over 10 years, compared to prospective matching. Perfectly informed antigen‐matching is more costly than history‐based matching, but reduces alloimmunization events by 45.6% over 10 years. Averting each alloimmunization event using this strategy would cost an additional $10, 934 per patient. Imperfectly informed antigen‐matching using an assay with 75% specificity and 75% sensitivity is less costly than prospective matching, but increases alloimmunization events. Compared to history‐based matching, imperfectly informed matching would decrease alloimmunization events by 32.61%, at an additional cost of $147, 915 per patient over 10 years. Cost‐effectiveness of informed antigen‐matching is largely driven by assay specificity. Conclusions A sufficiently specific assay to inform antigen‐matching may be cost‐effective in reducing alloimmunization among transfused patients with SCD.